Growing tall and dwarf rice cultivars in mixture for better weed management and higher yield: Growing tall and dwarf rice cultivars in mixture (Journal of the Bangladesh Agricultural University, 2019)
Growing two or more cultivars of same crop species in mixture reduces intra-specific competition for natural resources and increases competitive ability of crops against weeds and thus enhances crop yield. The objective of this study was to evaluate the potentiality of growing rice cultivars in mixtures for minimizing weed pressure and increasing rice yield. The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during Aman season (July-December) 2017. Two transplant Aman rice cultivars viz. Binadhan-13 (tall, late- maturing and fine grain aromatic cultivar) and BRRI dhan49 (semi-dwarf, mid-maturing and coarse grain cultivar) were grown following two spatial arrangements viz., alternate row and alternate hill, and nine different cultivar mixture (Binadhan-13:BRRI dhan49) row ratios viz., 1:0, 1:2, 2:1, 2:3, 3:2, 2:4, 4:2,1:1 and 0:1. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Results confirmed the positive influence of spatial arrangement and cultivar mixture ratio on rice productivity. Both the cultivars showed better growth and higher yield when grown in mixture irrespective of ratios compared to their sole culture performances. But cultivar mixture ratio showed no advantages over sole culture in suppressing weeds. Based on the total yield Binadhan-13 and BRRI dhan49 inter-planted in 1:1 row ratio following alternate hill performed the best resulting in 50% and 12% yield advantages over sole culture of Binadhan-13 and BRRI dhan49, respectively. Therefore, growing tall and dwarf rice cultivars in mixture can be adopted as a tool for increasing rice productivity.J. Bangladesh Agril. Univ. 17(2): 133–141, June 2019